Acute toxicities of three-dimensional conformal radiotherapy in the treatment of gynecological cancer, and retrospective dosimetric comparison of three dimensional conformal radiotherapy and invers intensity-modulated radiotherapy - Sağınç, Halil; Yıldırım, Özgür; Baltalarlı, Bahar (Journal of Surgery and Medicine, 2018)
Aim: The study was designed to compare the critical organ and bone marrow doses with three-dimensional conformal radiotherapy plans and intensity-modulated radiotherapy re-treatment plans and to evaluate acute toxicities of three-dimensional conformal radiotherapy for gynecological cancer. Methods: Twenty-eight patients who underwent conformal radiotherapy (3D-CRT) were evaluated retrospectively and were re- planned according to IMRT technique. The critical organ and bone marrow doses of patients were compared dosimetrically. Evaluation of early side effects was performed using RTOG toxicity scale and European Organization for Research and Treatment of Cancer (EORTC) QLQ30 side effect evaluation questionnaire. Results: The assessment of early toxicity revealed Grade 1 lower gastrointestinal (GIS) toxicity in 16 (57.1%) patients, grade 1 upper GIS toxicity in 9 (32.1%) patients, grade 1 hematological toxicity in one (3.6%) patients, grade 1 genitourinary toxicity in 15 (53.6%), grade 1 skin toxicity in (50%) 14 patients . One patient (3.6%) had grade 2 upper GIS toxicity, 11 patients (39.3%) had grade 2-3 hematological toxicity. Bone marrow V20 (p<0.001), V95 (%) of bone marrow (p<0.001), urinary bladder V40 (p<0.001), urinary bladder mean dose (p<0.001), rectum V40 (p<0.001), rectum mean dose (p<0.001), small bowel V40 (p<0.001) were received lower doses in the IMRT planning arm than the conformal planning arm. Conclusion: 3D-CRT is a safe treatment with acceptable low toxicity levels in gynecological cancer patients, and it does not adversely affect quality of life. IMRT reduce dose to the bone marrow and the normal tissues as compared to 3D-CRT.